THE INFLUENCE OF TARIQAS IN THE CONTEXT OF RELIGIOUS UNDERSTANDING AND THE STRENGTHENING OF LOCAL CULTURE MOBILITY IN ACEHNESE SOCIETY - Budiman, Iskandar (Indonesian Journal of Islamic Studies (IJIS), 2025)
Aceh is part of Indonesia’s archipelagic region and stands as the initial landing place of Islam. Situated on the western coast of Sumatra Island, this region played host to the peaceful introduction of Islam through Arab traders. The Islamization process, guided by a tasawwuf approach, unfolded smoothly, making it easy for the people of Aceh to embrace the Islamic faith. This underscores the significant role played by the tasawwuf approach and tariqa in the Islamization process. Consequently, the prevailing Islamic thought embraced by the community is infused with the practices of tasawwuf. Tariqa, etymologically meaning a method of practice to achieve a goal, has witnessed a notable increase in its development within the Islamic community. In Sufi terminology, “tariqa” is a form of spiritual practice and soul training aimed at attaining haqiqa (the essence) and ma'rifa (gnosis). These practices and exercises are guided by a spiritual teacher known as a “mursyid” (guide) because the journey between Sharia and haqiqa, according to Sufi scholars, must traverse seven great mountains. Islam significantly influences the way of life in Aceh society, with its people adhering firmly and with a commitment to religious teachings. In essence, Islam is a way of life for the people of Aceh. Over time, Acehnese society has changed its outlook on life. Some individuals practice specific tariqa to draw closer to the Creator. Tariqas such as Qadiriyya, Shattariyya, and Naqshbandiyya are among those that have developed in Indonesia. Engaging in the practices of these tariqas will influence the behavioral patterns of society. Moreover, the religious understanding among the community will change. In other words, the evolving tariqa brings a distinctive spiritual enthusiasm to the religious life of Acehnese society.